Korelasi Antara Hafalan Al-Qur’an Dengan Nilai Muhadatsah Bahasa Arab (An Naba, 2021)
The background of this research is the alignment of students’ Arabic conversation scores with the score of memorizing the al-Qur’an, so that researchers are interest in knowing how closely the relationship between memorizing Al-Qur'an and score of Arabic conversation at STIT Darul Fattah Bandar Lampung. This research is a quantitative type, this research design uses a correlation design. This research was conducted at STIT Darul Fattah Bandar Lampung. The research sample consisted of 20 students consisting of class A in first semester, which were determined using purposive sampling technique. The instruments consist of interviews and documentation.The data analysis technique uses simple correlation analysis techniques. Based on the calculation of the correlation coefficient with a significant level of 5% and 1%. With r count> r table or 0.717> 0.468 / 0.590, thus Ha is accepted. This means that there is a positive relationship / correlation between memorizing the Qur'an and score of Arabic Conversation of 0.717. There is a positive relationship between memorizing Al-Qur'an and score of Arabic Conversation students class A in second semester STIT Darul Fattah Bandar Lampung. The level of relationship or correlation between memorizing Al-Qur'an and score of Arabic Conversation in class A in second STIT Darul Fattah Bandar Lampung is in the strong category.